Unveiling yellow rust resistance in the near-Himalayan region: insights from a nested association mapping study - Jung, Katharina; Akiyama, Reiko; Nie, Jilu; Nitta, Miyuki; Hamaya, Naoto-Benjamin; Qureshi, Naeela; Bhavani, Sridhar; Wicker, Thomas; Keller, Beat; Kishii, Masahiro; Nasuda, Shuhei; Shimizu, Kentaro K. (Springer, 2025)
The global spread of yellow rust has posed a significant threat to wheat production, making the identification of novel resistance-conferring genetic loci crucial. The near-Himalayan region has been proposed as the pathogen's origin and is characterized by strong and diverse disease pressure. Even though this makes wheat varieties from this region likely to harbor resistance, Asian germplasm has been highly underrepresented in modern breeding. To explore this potential, we screened an Asian nested association mapping (NAM) population comprising traditional and modern wheat varieties under artificial epidemics in multiple field trials. Combined quantitative trait locus (QTL) mapping revealed the two resistance genes Lr67/Yr46/Sr55 and Lr34/Yr18/Sr57, as well as two potentially novel yellow rust resistance loci. The resistant allele of the first one, located on chromosome 3D, is unique to a traditional variety from Nepal, while the second one, found on chromosome 5B, is present in several NAM families. The broad geographic distribution of this QTL across regions with high disease pressure suggests it may serve as a durable source of resistance. Strong observed resistances were conferred by a combination of several resistance loci, suggesting the stacking of resistances as a successful strategy in yellow rust hotspot areas.